Actor-Subjects, their Voice, and their Relationship with the Mother Figure - Rasslan, Simone Nogueira; Fischer (Universidade Federal do Rio Grande do Sul – UFRGS, Porto Alegre/RS, Brazil), Rosa Maria Bueno (Revista Brasileira de Estudos da Presença, 2022)
This paper aims to investigate, employing Foucault’s archaeological approach, notions of subjectivity in which actors become subjects of their own musical practice, particularly of their vocal expression. The empirical materials are narratives and interviews with professionals from the performing arts, who execute the soundtracks of their live performances vocally and through the use of musical instruments. In this paper we analyze the predominant presence of the voice of the mother figure in the memories of actors-musicians.